Integrasi Media Digital dalam Meningkatkan Disiplin Belajar Pendidikan Agama Kristen (PAK) di Rumah dan Sekolah - Karina Onmilka; Elma Purwantie; Andreas Vicky Anugrahno P; Ronald Evandi Aden; Selfina Selfina; Yongki Pransoli; Matius Timan Hardi Ginting (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This paper explores the integration of digital media in enhancing students’ learning discipline within the context of Christian Religious Education (PAK), both at home and in school. In today’s digital era, digital media serves as a vital tool to support an interactive, flexible, and engaging learning process. Research indicates that digital media use can improve student motivation and engagement, which positively influences their study discipline. However, challenges such as limited technology access, low digital literacy, and potential distractions must also be addressed. The collaborative role of parents and educators is crucial in ensuring the effective use of digital media. Through this approach, digital media integration is expected to foster an adaptive, inclusive educational ecosystem that supports the development of student discipline and character.